Internal Integration of the Transition Economy: Evidence from Ukraine (Global Journal of Human-Social Science, 2013)
Based on the methodology suggested by Bowen, Munandar, and Viaene (2010; 2011) I examine the quantitative measurement of internal economic integration. For this purpose the link between the region's share in total output and production factors was estimated, the pattern of distribution of these shares among the regions of Ukraine was assessed. Calculations demonstrated an increasing tendency to deepen the internal integration of the Ukrainian economy, although 2009-2010 were characterized by a reduction in intra-regional economic integration.
Keywords: output distribution; production factor distribution; interregional economic integration